Report Failure in Applied Research and Social Program Evaluation: An Invitation to Epistemic Integrity - Cifuentes-Contador, S (SAGE Publications Ltd, 2023)
From a critical community psychology approach, this article seeks to visibilize social interventions that exhibit failings, thus exerting epistemic violence, by critically analyzing a microfinance project executed in India by an emblematic international research center of the Global North. Through fieldwork and interviews, we identified four shortcomings of the intervention: issues affecting the participants, implementation problems, limited effects of the project, and dissatisfaction with the intervention. This case illustrates how the prioritization of research objectives to the detriment of a proper implementation of the underlying social interventions constitutes epistemic violence as well as academic and epistemic extractivism. Based on this information, we intend to advance an expanded notion of epistemic violence, going beyond data analysis and taking into account the conditions of knowledge production in applied research, exemplified by a social program evaluation and their consequences for participants. This approach allows us to visibilize the importance of report failure and propose the concept of epistemic integrity, which is aimed at generating socially relevant knowledge while democratizing said knowledge, encouraging power redistribution, and promoting social justice. Regarding applied research, we discuss specific considerations for epistemic integrity. © The Author(s) 2023.